2008
DOI: 10.1128/aem.01143-08
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of xyr1 , Encoding the Main Regulator of the Xylanolytic and Cellulolytic Enzyme System in Hypocrea jecorina

Abstract: In Hypocrea jecorina, Xyr1 (xylanase regulator 1) is the main transcription activator of hydrolase-encoding genes, such as xyn1, xyn2, bxl1, cbh1, cbh2, egl1, and bgl1. Even though Xyr1 mediates the induction signal for all these genes derived from various inducing carbon sources and compounds, xyr1 transcription itself is not inducible by any of these substances. However, cultivation on glucose as the carbon source provokes carbon catabolite repression of xyr1 transcription mediated by Cre1. In addition, xyr1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
190
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(214 citation statements)
references
References 54 publications
17
190
3
4
Order By: Relevance
“…Furthermore, these results are in accordance with the finding that XlnR, the corresponding A. niger Xyr1 orthologue (23) (12). This is in accordance with our previous finding that, although the presence of Xyr1 is indispensable for xyn1 expression (20), no de novo synthesis of Xyr1 is needed for initial xyn1 induction in H. jecorina (8).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, these results are in accordance with the finding that XlnR, the corresponding A. niger Xyr1 orthologue (23) (12). This is in accordance with our previous finding that, although the presence of Xyr1 is indispensable for xyn1 expression (20), no de novo synthesis of Xyr1 is needed for initial xyn1 induction in H. jecorina (8).…”
Section: Discussionsupporting
confidence: 82%
“…We have previously reported that transcription of xyr1, the central activator of hydrolase expression in H. jecorina, does not respond to induction by a specific carbon source (8). In this study, we confirmed our observation by demonstrating similar xyr1 transcription levels under all conditions and strains tested.…”
Section: Discussionsupporting
confidence: 81%
“…Xylanase production in xylan cultures of a T. reesei strain constitutively expressing the xylanolytic activator Xyr1 was also shown to be greater than that of the wild type at relatively early culture stages (about four times after 48 hours), though the maximum levels of activity achieved by both strains were similar after 72 hours [36]. Characteristics specific to each fungal species (for example protein folding, secretory ability and protease activity), differences in XlnR/Xyr1 expression levels, different requirements for XlnR/Xyr1 of the xylanolytic gene promoters and/or differences in the culture conditions (such as the use of distinct inducers) might account for the differences in improvements reported in each study.…”
Section: Resultsmentioning
confidence: 98%
“…xyn1 and xyn2 were previously reported to be subject to regulation by the C 2 H 2 carbon catabolite repressor CRE1 via a doublelock mechanism (19,38) that controls xylanase transcription at two different levels, by direct repression through CRE1, and indirectly through the CRE1-mediated repression of the transcriptional activator XYR1 (39). Binding sites for the carbon catabolite repressor CRE1 are present in all xylanase genes ( Fig.…”
Section: Resultsmentioning
confidence: 99%